Islam and Muslim Politics in Africa - Soares, B. author. aut Link
IX, 280 p.
Keywords: Political liberalization and economic reform, the weakening of the state, and increased global interconnections have all had profound effects on Muslim societies and the practice of Islam in Africa. The contributors to this volume investigate and illuminate the changes that have occurred in Africa, through detailed case studies.